Structure and functions of the European parliament after 2004 enlargement - Çetinkaya, Dilek (My University, 2006)
This is a study about the structure and the functions of the European Parliament after the 2004 enlargement of the European Union. Initially it explores the historical background and institutional framework of the European Union, closely inspecting the treaty reforms influencing the European Parliament. It continues with the close inspection of the structure, powers and responsibilities of the European Parliament and with the study of two major events in 2004 having a great influence over the European Parliament, which are, namely, the 2004 enlargement of the European Union and the 2004 European Parliament elections. As a conclusion, the study argues that the 2004 enlargement poses new challenges for the European Parliament and that it may cause a certain level of slow–down in the decision–making process within the European Parliament.

Bu çalışma, Avrupa Birliği’nin 2004 Genişlemesinden sonra Avrupa Parlamentosu’nun yapısını ve işlevlerini incelemektedir. Çalışmanın ilk bölümünde Avrupa Birliği’nin tarihsel gelişimi ve kurumsal yapısı ele alınmış ve özellikle Avupa Parlamentosu’nu etkileyen reformlar üzerinde durulmuştur. Ardından, Avrupa Parlamento’sunun yapısı, yetkileri ve görevleri incelenmiş ve 2004 yılında Avrupa Birliğini etkileyen iki önemli olay, sırasıyla Avrupa Birliği’nin 2004 Genişlemesi ve 2004 Avrupa Parlamentosu seçimleri ele alınmıştır. Çalışmanın sonuç bölümünde, 2004 Genişlemesinin Avrupa Parlamentosu için yeni sorunlar yarattığı ve Avrupa Parlamentosu içindeki karar alma süreci üzerinde belli düzeyde bir yavaşlama yaratabileceği savunulmaktadır.
Keywords: Avrupa Birliği; Avrupa Parlamentosu